1998
DOI: 10.1002/(sici)1521-4141(199802)28:02<755::aid-immu755>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

The structural basis of MHC control of collagen-induced arthritis; binding of the immunodominant type II collagen 256 – 270 glycopeptide to H-2Aq and H-2Ap molecules

Abstract: The Aq major histocompatibility complex (MHC) class II molecule is associated with susceptibility to murine collagen-induced arthritis (CIA), whereas the closely related H-2Ap molecule is not. To understand the molecular basis for this difference, we have analyzed the ability of H-2Aq and H-2Ap molecules (referred to as Aq and Ap) to bind and present collagen type II (CII)-derived glycosylated and non-glycosylated peptides. T cell clones specific for the immunodominant CII 256-270 peptide and restricted to bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
84
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 82 publications
(96 citation statements)
references
References 35 publications
11
84
0
Order By: Relevance
“…1C), showed signals that were assigned to E-peptide (m/z 1476.766, shifted to 11 Da, deamidated Q) and cross-links between Q-peptides (m/z 2933.532). The MS data prove that both TG-mediated modifications, deamidation and cross-link formation, could be obtained after treatment of Previous studies have shown that amino acid residues I 260 and F 263 from the immunodominant epitope CII259-273 are the major MHC anchor residues occupying the P1 and P4 pockets of the I-A q molecule [29,30], and posttranslational modifications at position K 264 (hydroxylation and glycosylation) did not affect I-A q binding [30]. All these studies suggested that Q 267 from the immunodominant epitope is a TCR contact residue.…”
Section: Separation and Identification Of Ttg-mediated Modifications supporting
confidence: 55%
See 1 more Smart Citation
“…1C), showed signals that were assigned to E-peptide (m/z 1476.766, shifted to 11 Da, deamidated Q) and cross-links between Q-peptides (m/z 2933.532). The MS data prove that both TG-mediated modifications, deamidation and cross-link formation, could be obtained after treatment of Previous studies have shown that amino acid residues I 260 and F 263 from the immunodominant epitope CII259-273 are the major MHC anchor residues occupying the P1 and P4 pockets of the I-A q molecule [29,30], and posttranslational modifications at position K 264 (hydroxylation and glycosylation) did not affect I-A q binding [30]. All these studies suggested that Q 267 from the immunodominant epitope is a TCR contact residue.…”
Section: Separation and Identification Of Ttg-mediated Modifications supporting
confidence: 55%
“…The peptide binding assay was performed by measurement of the ability of synthetic peptides (Q-and E-peptides) to inhibit the binding of biotinylated CLIP-peptide to purified MHC class II molecules as described [30] with slight modifications. In brief, a mixture of a fixed concentration of purified soluble recombinant I-A q molecules (0.1 mM), biotinylated CLIP peptide (2.5 mM), and increasing concentrations of competitor peptides (0, 0.8, 4, 20, 100 and 500 mM) was incubated for 48 h at room temperature and in the presence of a protease inhibitor cocktail (Complete TM , Roche Diagnostics GmbH, Mannheim, Germany).…”
Section: Mhc-peptide Binding Assaymentioning
confidence: 99%
“…It is thought that T and B cell responses to this autoantigen are associated with the development and pathogenesis of rheumatoid arthritis (RA) [2,3]. It is also widely believed that RA is genetically linked to HLA class II molecules, including some HLA-DR4 alleles, and that T cell responses in collagendependent RA are directed towards the immunodominant pathogenic epitope CII [261][262][263][264][265][266][267][268][269][270][271][272][273] [4,5]. Studies also suggest that T cells from patients with RA predominantly recognize the glycosylated form of the immunodominant CII peptide [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Studies also suggest that T cells from patients with RA predominantly recognize the glycosylated form of the immunodominant CII peptide [6,7]. Professional antigen-presenting cells (APC) such as B cells, macrophages and dendritic cells abundantly express HLA class II proteins and play critical roles in the pathogenesis of autoimmune arthritis by presenting autoantigens to T cells [4,5,8].In RA, cartilage proteins including CII undergo degradation by proteases, leading to the generation of peptides that can bind to HLA class II proteins and trigger CD4 + T cell activation [9]. Studies suggest that the peptides are loaded onto class II proteins Eur.…”
mentioning
confidence: 99%
“…The T cell response is directed towards the same immunodominant core, CII residues 260-270 [9,10]. This T cell determinant contains lysine residues at position 264 and 270, which can become posttranslationally modified by hydroxylation and further galactosylated and glucosylated, creating many different epitopes containing hydroxyl, mono-and disaccharide groups in both RA and CIA.…”
Section: Introductionmentioning
confidence: 99%